2003
DOI: 10.1200/jco.2003.12.109
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Efficacy of Trastuzumab Administered Every Three Weeks in Combination With Paclitaxel

Abstract: Additional investigation of trastuzumab administered every 3 weeks is warranted. In combination with paclitaxel, it is generally well tolerated. Plasma trastuzumab trough levels and clinical response rates compare favorably with those achieved with the standard weekly trastuzumab regimen plus chemotherapy. The presence of trastuzumab does not alter exposure to paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(118 citation statements)
references
References 20 publications
6
106
0
6
Order By: Relevance
“…The results of our study show that pharmacokinetics of cyclophosphamide, cisplatin, and BCNU, administered at high doses, are not altered in the presence of trastuzumab. Previous reports indicated that the pharmacokinetics of trastuzumab are not affected by the presence of chemotherapy drugs (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study show that pharmacokinetics of cyclophosphamide, cisplatin, and BCNU, administered at high doses, are not altered in the presence of trastuzumab. Previous reports indicated that the pharmacokinetics of trastuzumab are not affected by the presence of chemotherapy drugs (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important, given the cardiotoxic side effects of trastuzumab seen in approximately 1.4% of patients receiving the drug as a single agent, 36,42,43 and even in higher percentages of patients receiving trastuzumab concomitantly with paclitaxel (13%) or anthracyclines (27%), 37 as well as the high cost of the drug. 44,45 HER2 IHC poses even greater challenges than does ER IHC, as both accurate as well as semi-quantitative assessment of the results of HER2 immunostaining are critical.…”
Section: Part 2: Human Epidermal Receptor Protein-2mentioning
confidence: 99%
“…This is particularly important given the cardiotoxic side effects of trastuzumab seen in approximately 1.4% of patients receiving the drug as a single agent, 10,16,17 and in even higher percentages of patients receiving trastuzumab concomitantly with paclitaxel (13%) or anthracyclines (27%), 11 as well as the high cost of the drug. 18,19 Although a tight association between HER2 gene amplification and protein overexpression has been documented in breast cancers by western and northern blot analyses, 20 Press et al 21 have demonstrated that immunohistochemistry (IHC) on deparaffinized, formalin-fixed tissue can be quite variable in its ability to identify HER2-amplified tumors.…”
mentioning
confidence: 99%